PENENTUAN KONSTANTA OPTIS DI DAERAH ABSORPSI FUNDAMENTAL MENGGUNAKAN FORMULASI FOROUHI DAN BLOOMER UNTUK LAPISAN TIPIS AMORF SILIKON KARBON (a-SiC:H) - Saleh, Rosari; Munisa, Lusitra; Marianty, Dewi (UI Scholars Hub, 2002)
An expression of the imaginary and real parts of the complex refractive index derived by Forouhi and Bloomer have been applied to obtain wider energy range of optical constants for amorphous silicon carbon (a-SiC:H) films deposited by dc sputtering method using silicon and graphite targets. Excellent agreement was obtained between the formula and experimentally measured values of both n(E) and k(E). The optical constants obey Kramers-Kronig dispersion relation and show a maximum at high-energy range. The dependence of five parameters to carbon concentration and the variation of optical constants with composition for both targets will be discussed.